Premenstrual Syndrome and Associated Factors among Students in Secondary Schools in Arba Minch Town, Southern Ethiopia: A Cross-Sectional Study, 2021 - Ali Momina; Dejene Yesuneh; Gultie Teklemariam; Gebreselassie Rediet; Hailu Mickiale; Kebede Abebaw (Journal of Women's Reproductive Health, 2023)
Background Many women feel physical or mood changes in the days before menstruation. Previous studies in other areas of Ethiopia have not looked at factors that could be related to the premenstrual syndrome. As a result, this study aims to fill these gaps by determining the prevalence and behavioral, reproductive, and menstrual factors that affect premenstrual syndrome in Arba Minch town. Methods An institution-based cross-sectional survey was conducted in Arba Minch town from April 1 to April 25, 2021. Participants were chosen using computerized simple random selection from a list of female students' registration numbers that had been transformed into unique codes. SPSS for Windows version 25.0 was used to analyze and interpret the data. Bivariate analysis was used to fit variables with a P-value of less than 0.2 for multivariable analysis. In multivariable logistic regression, variables with a P-value less than 0.05 are considered statistically significant. Result This study has revealed that 59.8% (95% CI: 55.8%–63.8%) of students have premenstrual syndrome. Dysmenorrhea (AOR = 3.172, 95% CI: 2.032, 4.952), family history of PMS (AOR = 3.155, 95% CI: 2.119, 4.697), normal body mass index (AOR = 0.244, 95% CI: 0.161, 0.37), and overweight (AOR = 3.739, 95% CI: 1.763, 7.931) were significantly associated with premenstrual syndrome. This study has revealed that 59.8% (95% CI: 55.8%–63.8%) of students have premenstrual syndrome. Dysmenorrhea (AOR = 3.172, 95% CI: 2.032, 4.952), family history of PMS (AOR = 3.155, 95% CI: 2.119, 4.697), normal body mass index (AOR = 0.244, 95% CI: 0.161, 0.37), and overweight (AOR = 3.739, 95% CI: 1.763, 7.931) were significantly associated with premenstrual syndrome. Conclusion Six out of ten Arba Minch town secondary school students had premenstrual syndrome. Dysmenorrhea, a family history of premenstrual syndrome, and body mass index were found to be significantly associated.
Keywords: Association